Production of starch nanoparticles by dissolution and non-solvent precipitation for use in food-grade Pickering emulsions. (10th February 2017) - Saari, Hisfazilah; Fuentes, Catalina; Sjöö, Malin; Rayner, Marilyn; Wahlgren, Marie
Highlights: Non-solvent precipitation technology that gave 70% of starch particles below 1 μm. Particle characterization using several methods showed particles around 200 nm. Pickering emulsions with a droplet size of 10 μm obtained with 200 mg starch/mL oil. Low oil content with emulsion index of 1 for emulsions with 5% oil. As low amount (1 mg Starch/mL oil) is able to create emulsion (35 μm droplet size). Abstract: The aim of this study was to investigate non-solvent precipitation of starch to produce nanoparticles that could be used in Pickering emulsions. The material used was waxy maize, modified with octenyl succinic anhydride. Different methods of non-solvent precipitation were investigated, and a method based on direct mixing of an 8% starch solution and ethanol (ratio 1:1) was found to produce the smallest particles. The particle size was measured using AFM and AF4, and was found to be in the range 100–200 nm. However, both larger particles and aggregates of nanoparticles were observed. The emulsion produced using the precipitated starch particles had a droplet size that between 0.5 and 45 μm, compared to emulsions produced from waxy maize granules, in which had a size of 10–100 μm. The drop in size contributed to increased stability against creaming. The amount of starch used for emulsion stabilization could also be substantially reduced.